Labor market discrimination in Lima, Peru: evidence from a field experiment - Galarza, Francisco (2012)
Latin America is seen as a highly discriminatory society. However, such a common belief appears not to be based on strong empirical evidence (Chong and Ñopo, 2007). This paper exploits novel experimental data gathered to identify the existence of discrimination in the labor market of Lima, Peru, a fast-growing country where much anecdotal evidence suggests the presence of discriminatory practices at many instances of daily life. Focusing on two dimensions, sex (female/male) and surnames (indigenous/white), we sent 4,820 fictitious and equivalent CVs in response to 1,205 real job vacancies advertised in an important Peruvian newspaper. We randomly allocated indigenous and white surnames across CVs sent in application to professional, technical, and unskilled jobs. Overall, we find that males receive 20 percent more callbacks than females, and whites receive 80 percent more calls than indigenous applicants. Within job categories, we find sexual discrimination only in unskilled jobs, while discrimination against indigenous is verified across all job categories. There are no statistically significant differences in the time to receive a phone call among male/female, and white/indigenous applicants.